Implementasi Program Desa Ramah Perempuan Dan Peduli Anak (DRPPA) di Desa Tinelo Kecamatan Tilango - Ariandi Saputra; Prahara Prahara; Swastiani Dunggio (Program Studi Ilmu Pemerintahan, 2026)
This study aims to examine the implementation of the Women-Friendly and Child-Caring Village (DRPPA) program in Tinelo Village, Tilango District. This research employs a qualitative descriptive approach with a case study method. The results indicate that the prevention programs for violence against women and childre conducted through communication, information, and education by the DRPPA in the form of socialization have been implemented effectively. Furthermore, the overall implementation of policies regarding the prevention of violence against women and children in Tinelo Village’s DRPPA is proceeding well. This is evidenced by the effective communication established between policymakers and policy implementers, as well as among the implementers of the child violence prevention program within the DRPPA of Tinelo Village.